Responsiveness of the anterior cruciate ligament - return to sports after injury (ACL-RSI) and injury - psychological readiness to return to sport (I-PRRS) scales - Slagers, A.; Zwerver, J. (British Journal of Sports Medicine, 2021)
Background Both physical and psychological readiness are important for a successful return to sport (RTS) and secondary prevention. The ACL-Return to Sport after Injury (ACL-RSI) and Injury-Psychological Readiness to Return to Sport (I-PRRS) scales were developed to assess psychological factors associated with RTS. Validity and reliability have been determined but responsiveness of both scales has not been examined yet.